2015
DOI: 10.1152/ajpheart.00106.2015
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinase expression is altered in cardiac and skeletal muscle in cancer cachexia

Abstract: Cardiac and skeletal muscle dysfunction is a recognized effect of cancerinduced cachexia, with alterations in heart function leading to heart failure and negatively impacting patient morbidity. Cachexia is a complex and multifaceted disease state with several potential contributors to cardiac and skeletal muscle dysfunction. Matrix metalloproteinases (MMPs) are a family of enzymes capable of degrading components of the extracellular matrix (ECM). Changes to the ECM cause disruption both in the connections betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
1
25
1
Order By: Relevance
“…Zymography analysis of gastrocnemius evidenced a significant increase of proteolytic activity with contribution of MMPs. The activation of MMP-2 and MMP-9 in skeletal muscle was previously reported in atrophic conditions(37), and associated with the disruption of the connections between cells at the basement membrane and of cell-to-cell interactions(38). Data supports an increased expression and activity of MMP-2 in PAH-related muscle wasting, though without the participation of MMP-9, in opposition to what happened in bladder cancer-related muscle wasting(15).…”
mentioning
confidence: 55%
“…Zymography analysis of gastrocnemius evidenced a significant increase of proteolytic activity with contribution of MMPs. The activation of MMP-2 and MMP-9 in skeletal muscle was previously reported in atrophic conditions(37), and associated with the disruption of the connections between cells at the basement membrane and of cell-to-cell interactions(38). Data supports an increased expression and activity of MMP-2 in PAH-related muscle wasting, though without the participation of MMP-9, in opposition to what happened in bladder cancer-related muscle wasting(15).…”
mentioning
confidence: 55%
“…In previous studies it has been shown that there is increased collagen deposition in the hearts of c26 tumor-bearing mice through Picrosirius red staining [14]. The study did not examine the RNA expression of collagen, which we examined in this study.…”
Section: Discussionmentioning
confidence: 98%
“…The gel was transferred onto a PVDF membrane using a wet transfer system (Bio-Rad, Hercules, CA) that was run at room temperature for 90 minutes at 100 V. The membranes were blocked for 1 hour at room temperature with a TBS-T solution containing 5% Bovine Serum Albumin (BSA). The primary antibody was suspended at the same concentration as previously [14] used and incubated overnight at 4°C. The membrane was washed in TBST in triplicate for five minutes, then secondary antibody was applied at a concentration of 1:5000 in TBST containing 2.5% BSA for an hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-2, MMP-3, and MMP-14, which degrade components of the ECM and are associated with pathology in models of heart failure and muscular dystrophy, have been shown to be induced in cardiac and skeletal muscle in the Colon26 mouse model of cancer cachexia (Devine et al, 2015). Cardiac fibrosis is also noted.…”
Section: Fibrosis and Adipose Tissue Stiffness In Wastingmentioning
confidence: 99%